Remark
The easiest way to do this would be to substitute all values into the given equation. The best way is probably to translate the equation into the slope form equation.
Since you may not know the slope y intercept form, I'll just do it by substitution into the give equation. The left and right sides should be equal.
Solution.
y - 4 = 3(x + 2) use 2,4
4 - 4 = 3(2 + 1)
0 <> 12 So A is not the answer.
y - 4 = 3(x + 2) use 4,-2
-2 - 4 =3(4 +2)
- 6 = 18 B is not the answer.
y - 4 = 3(x + 2) use -2,4
4 - 4 = 3(-2 + 2) Here we are.
0 = 3*0
0 = 0
y - 4 = 3(x + 2) use -4,2
2 - 4 = 3(-4 + 2)
-2 = -6 which is not true so D does not work.